Autoantibodies in movement and psychiatric disorders: updated concepts in detection methods, pathogenicity, and CNS entry. (17th June 2015) - Sinmaz, Nese; Amatoury, Mazen; Merheb, Vera; Ramanathan, Sudarshini; Dale, Russell C.; Brilot, Fabienne
Abstract : In recent years, autoantibodies to proteins or receptors expressed on the surface of neurons have been detected in movement and psychiatric disorders. These autoantibodies can assist in better recognition of clinical syndromes and offer novel treatment opportunities via immunotherapies, potentially leading to improved patient outcome. In this review, we describe several autoimmune syndromes associated with movement and psychiatric disorders, including anti‐ N ‐methyl‐d ‐aspartate receptor encephalitis, basal ganglia encephalitis, Sydenham chorea, and autoantibody‐associated psychosis and schizophrenia. However, rather than focusing on clinical aspects of these diseases, as they have been reviewed in detail elsewhere, we mainly focus on the scientific aspects of the different methodologies for detecting antibodies, with an emphasis on the current gold standard in the field, the cell‐based assay, and on issues related to the use of live versus permeabilized cells. We also reflect on the implications associated with the choice of patient serum and cerebrospinal fluid for antibody testing, on the mechanism of antibody entry into the central nervous system through the blood–brain barrier, and the essential issue of antibody pathogenicity.